2001
DOI: 10.4269/ajtmh.2001.65.125
|View full text |Cite
|
Sign up to set email alerts
|

Probability of Trypanosoma cruzi transmission by Triatoma infestans (Hemiptera: Reduviidae) to the opossum Didelphis albiventris (Marsupialia: Didelphidae).

Abstract: Abstract. The probability of Trypanosoma cruzi transmission to opossums by independent events of predation and fecal contamination during feeding (''biting'') with positive Triatoma infestans was estimated. Negative female opossums were challenged for 23 hr with 10 infected third and fourth instars of T. infestans, and tests for positivity for T. cruzi by xenodiagnosis were performed at 30, 60, and 90 days. From these data, seven probability parameters were estimated by maximum likelihood, and likelihood ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…Both opossums and skunks may acquire T. cruzi infection by eating infected T. infestans, either when they approach houses in search for food, or when adult bugs eventually disperse by flight into sylvatic habitats, or by contamination with bug feces. The probability of experimental opossum infection with T. cruzi by ingestion or contamination was about 6-8% (Rabinovich et al, 2001). Regardless of the exact mechanism and habitat where vector-mediated transmission occurs, if domestic or peridomestic T. infestans infected with T. cruzi were implicated in opossum infections, the observed major decrease in the extent and abundance of infected bugs would imply an insignificant risk of infection for local opossums.…”
Section: Discussionmentioning
confidence: 99%
“…Both opossums and skunks may acquire T. cruzi infection by eating infected T. infestans, either when they approach houses in search for food, or when adult bugs eventually disperse by flight into sylvatic habitats, or by contamination with bug feces. The probability of experimental opossum infection with T. cruzi by ingestion or contamination was about 6-8% (Rabinovich et al, 2001). Regardless of the exact mechanism and habitat where vector-mediated transmission occurs, if domestic or peridomestic T. infestans infected with T. cruzi were implicated in opossum infections, the observed major decrease in the extent and abundance of infected bugs would imply an insignificant risk of infection for local opossums.…”
Section: Discussionmentioning
confidence: 99%
“…The only other two reports of observed oral transmission probability involved opossums and different parasite strains, and generated much lower estimates of 0.075 [37] and 0.15 [49]; the differences in host biology, vector species and parasite strain make it difficult to extend them to the two cycles under study here but may signal significant differences in oral transmissibility by strain and/or host. In the scenario in the main text which assumes no adaptation to/from oral transmissibility (AOT), we can take the weighted (by sample size) average of 0.177 from [23].…”
Section: Appendix 1 Parameter Estimationmentioning
confidence: 94%
“…Vertical (congenital) transmission, which has been observed in humans as well as laboratory rats [28,43], may also be significant among other placental hosts (but not in marsupials such as opossums). Furthermore, it has been suggested that oral transmission of T. cruzi via host consumption of infected vectors (raccoons and opossums are both opportunistic feeders whose diets include insects) may be the dominant infection pathway in some cycles, more likely among raccoons than among opossums [32,37,40,49]. Oral transmission has also been documented in laboratory mice as well as in humans [4,7] and other primates [35].…”
Section: Introductionmentioning
confidence: 99%
“…Vertical transmission has been reported among placental hosts such as rats and mice [22,23], and humans [24]. In addition, sylvatic hosts such as raccoons and opossums are opportunistic feeders whose diet includes insects, and experimental studies have shown that they can get infected by ingesting infected vectors [25,26]. Oral transmission of T. cruzi is likely to be a dominant transmission pathway for sylvatic T. cruzi in the SE US, and explain the high disease prevalence observed among raccoons in particular [27], as suggested by the model of [13].…”
Section: Introductionmentioning
confidence: 99%